Aligning Distribution Centre Operations to Supply Chain Strategy. - Baker, Peter (Emerald, 2004)
A major focus of modern day logistics is on achieving a higher level of responsiveness to marketplace demand, but with less inventory. Achieving the dual targets of lower cost and higher service has implications for every stage in the supply chain and in particular for distribution center operations. What is the extent to which organizations are adjusting their distribution center operations to match current supply chain concepts? Using a survey, roles that these facilities play are explored in order to determine the extent to which modern supply chain theory and distribution center operations are aligned.
Keywords: Distribution and inventory management; Distribution centres; Supply-chain management